STUDI KELAYAKAN PANTAI BATU MEJAN SEBAGAI PRODUK WISATA DI SURABRATA, KABUPATEN TABANAN - Sridewi, Ni Putu Ayu Ari; Adikampana, I Made (JURNAL DESTINASI PARIWISATA, 2013)
ABSTRACT Surabrata is part of Lalanglinggah Village area which has a lot of natural resources. One of them is the Batu Mejan beach. Batu Mejan is one of the beaches with black sand. In addition, these beach also has a moving cape (in Indonesian famous with Tanjung Bergetar). The attractions are quite unique and beautiful. However,  the support of local  government to develop these tourism product in still lack. This research is to analyze the potential and feasibility study of Batu mejan beach as a touristm product. The data are collected by observation and interviews. The descriptive qualitative analysis is used to get the feasibility of tourism development. The result of the study shows that Batu Mejan beach developed as a tourism product of sixth tourist product characteristics and components of tourism products contained on the Batu Mejan beach.
Keywords: Keywords: Feasibility Study, Tourism Products, Batu Mejan Beach